Risk factors associated with preterm delivery after fetoscopic laser ablation for twin–twin transfusion syndrome. (January 2014) - Papanna, R.; Block‐Abraham, D.; Mann, L. K.; Buhimschi, I. A.; Bebbington, M.; Garcia, E.; Kahlek, N.; Harman, C.; Johnson, A.; Baschat, A.; Moise, K. J.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014:43:11–12